2001
DOI: 10.1093/emboj/20.18.5049
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional reconstitution of the yeast peroxisomal adenine nucleotide transporter

Abstract: The requirement for small molecule transport systems across the peroxisomal membrane has previously been postulated, but not directly proven. Here we report the identification and functional reconstitution of Ant1p (Ypr128cp), a peroxisomal transporter in the yeast Saccharomyces cerevisiae, which has the characteristic sequence features of the mitochondrial carrier family. Ant1p was found to be an integral protein of the peroxisomal membrane and expression of ANT1 was oleic acid inducible. Targeting of Ant1p t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
208
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(219 citation statements)
references
References 57 publications
9
208
1
1
Order By: Relevance
“…However, today we know that the presence of MCF proteins is by no means restricted to mitochondrial membranes (51). The recent discovery of MCF-type nucleotide transporters in peroxisomes (7,18,52), plant plastids (19,20,23), and the endoplasmic reticulum of Arabidopsis (21) strikingly demonstrates that several organelles, especially in plant cells, exploit the large pool of MCF proteins to facilitate cross-membrane nucleotide transport. Thus, with our observation that AtNDT1-GFP resides in the chloroplast envelope (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, today we know that the presence of MCF proteins is by no means restricted to mitochondrial membranes (51). The recent discovery of MCF-type nucleotide transporters in peroxisomes (7,18,52), plant plastids (19,20,23), and the endoplasmic reticulum of Arabidopsis (21) strikingly demonstrates that several organelles, especially in plant cells, exploit the large pool of MCF proteins to facilitate cross-membrane nucleotide transport. Thus, with our observation that AtNDT1-GFP resides in the chloroplast envelope (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent member is the mitochondrial ADP/ATP carrier AAC (4), but MCF-type nucleotide transporters have also been identified in peroxisomes (7,18), in plastids (19,20), and in the endoplasmic reticulum of higher plants (21). The transport modes catalyzed by MCF-type adenylate nucleotide transporters range from typical ADP/ATP counterexchange in mitochondria (4) to ATP/AMP exchange in peroxisomes (7,18) and in Arabidopsis mitochondria (22) range from ADP-glucose/ADP exchange in maize endosperm amyloplasts (23) to unidirectional adenylate export from plastids (20,23).…”
mentioning
confidence: 99%
“…Recently, another MCF member was demonstrated to function as a plastidic folate transporter (Bedhomme et al, 2005), and other MCF members have been shown to be involved in adenine nucleotide uniport into plastids (Leroch et al, 2005) and in the uptake of ADP-glucose into maize (Zea mays) endosperm plastids (Sullivan and Kaneko, 1995). Moreover, a yeast peroxisomal ATP transporter also belongs to the MCF (Palmieri et al, 2001), (E) RT-PCR analysis of the transcript level of Nb SAMT1. Primers annealing outside of the TTO-Nb SAMT1 construct were used.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent works suggest that, in vivo, the membrane is rather impermeable to NAD(H) and acetyl-CoA . ATP for its part has been shown to enter the peroxisomal lumen through the action of a transporter (Palmieri et al 2001), in the absence of which medium-chain (but not long-chain) fatty acids could not be activated into acyl-CoA (Van Roermund et al 2001). …”
Section: Transport To the Peroxisomesmentioning
confidence: 99%